Elemental distribution of core marine sediments in the coast of Sabah, Malaysia by using neutron activation analysis and inductively coupled plasma spectroscopy - Ashraf, Ahmadreza (2015)
Sabah of Malaysia shares the island of Borneo with Sarawak, Brunei and Indonesian Kalimantan. The shoreline for Sabah is around 1802 km in length. Contamination of heavy metals have occurred in the sea of Sabah from natural weathering and human activities in land including home and industrial wastes and also agricultural runoff such as nutrients, pesticides and fertilizers. The present research was an investigation on the vertical distribution of the concentrations of heavy metals, trace elements, rare earth elements, major elements and actinides from the core marine sediment samples in the coastal areas of Sabah. The study could provide baseline data of these element compositions in the sea of Sabah for future reference. The elemental concentrations were acquired by using Instrumental Neutron Activation Analysis (INAA) and Inductively Coupled Plasma-Mass Spectroscopy (ICP-MS) method. Generally, all elements were determined and they were further categorized as heavy metals, trace elements, rare earth elements, major elements and actinide elements based on their physical and chemical characteristics. There are 30 elements, including 24 elements (namely, Th, U, Zn, Al, Ca, Fe, K, Mg, Mn, Na, Ce, Lu, Dy, Sm, Eu, Yb, La, Sc, Br, Rb, Cs, Ta, Hf, and V), which were studied by using Instrumental Neutron Activation Analysis (INAA) and the following 6 elements (namely, As, Cd, Cu, Ni, Pb, and Cr) were studied by using Inductively Coupled Plasma-Mass Spectroscopy (ICP-MS) technique. The degrees of enrichment and the status of contamination are categorized as the enrichment factor, geo-accumulation index and the modified degree of contamination methods were used to interpret the results. Furthermore, Pearson’s correlation factors and a cluster analysis were also carried out to determine the associations between the variables. The anthropogenicity of the elements was assessed using Kolmogorov-Smirnov tests and box plot tests. The anthropogenity of the elements was tested at 95% confidence level. For the core elemental distributions of heavy metals (As, Cd, Cr, Cu, Ni, Pb, and Zn), the elements Cr, Ni, Pb and Zn showed the elemental concentrations exceeding 10 mg/kg in most stations and at all sampling depths. However, the enrichment factors of As are between 2 and 5 for SB1, SB2, and SB3, which revealed a moderate enrichment in the west coast of Sabah. Other elements were minimal enrichements for all the samples. Other contamination analyses indicated that all heavy metals were unpolluted for all sampling stations of Sabah. . For trace elements (Br, Cs, Hf, Rb, Ta, V), the elements Br, Rb and V showed the elemental concentrations exceeding 20 mg/kg in most stations and at all depths. However, the enrichment factors of Hf exceeded 2 at most stations, which revealed a moderate enrichment in the west coast of Sabah except at SB5. Other elements were minimal enrichements for all the samples. All trace elements were unpolluted for all sampling stations in Sabah analyzed by other contamination analysis methods. For light rare earth elements-LREEs (Sc, La, Ce, Sm, and Eu) and heavy rare earth elementsHREEs (Dy, Yb, and Lu), the LREEs at all stations were found to be averagely ten times higher than HREEs. However, all rare earth elements were unpolluted for all sampling stations in Sabah. For major elements (Al, Fe, Ca, K, Mg, Na, aand Mn) showed the elemental concentrations exceeding 10,000 mg/kg in all stations and at most sampling depths except for Mn where the elemental concentrations below 700 mg/kg in all stations and at all sampling depths. Only Ca and Na were polluted elements for all sampling stations. The contamination is contributed likely from natural sources, i.e marine animal skeletons for Ca and sea water for Na. For actinide elements (Th and U) are unpolluted by other contamination analysis methods except for U in SB2, SB3, and SB4 stations disclosed moderate enrichment analysis.